1999
DOI: 10.1016/s0168-1702(99)00029-5
|View full text |Cite
|
Sign up to set email alerts
|

Recombination between North American strains of porcine reproductive and respiratory syndrome virus

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV), a recently discovered arterivirus swine pathogen, was shown to undergo homologous recombination. Co-infection of MA-104 cells with two culture-adapted North American PRRSV strains resulted in recombinant viral particles containing chimeric ORF 3 and ORF 4 proteins. Nucleotide sequence analysis of cloned recombinant PCR products, encompassing 1182 bases of the 15.4 kb viral genome, revealed six independent recombination events. Recombinant products pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 27 publications
2
91
0
Order By: Relevance
“…Furthermore, the finding of a field virus which had undergone recombination with a vaccine or vaccine-like virus highlights an additional mechanism for the generation of ever-more diverse viruses. Such recombination events between field strains have previously been proposed for PRRSV (Yuan et al, 1999;Forsberg et al, 2002;Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, the finding of a field virus which had undergone recombination with a vaccine or vaccine-like virus highlights an additional mechanism for the generation of ever-more diverse viruses. Such recombination events between field strains have previously been proposed for PRRSV (Yuan et al, 1999;Forsberg et al, 2002;Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, phylogenetic analysis of nucleotide sequences of three separate ORFs (3, 5, and 7) from 13-US, 14-US, 15-US, and EuroPRRSV provided no evidence of recombination with type 2 isolates. If intertype RNA recombinants are generated at a low level under field conditions, it is likely that such recombinants would not be viable due to the low level of similarity between the strains (73) or that one of the original virus isolates would eventually dominate the intertype recombinant, as observed in cell culture (81). However, preexisting immunity to the parental viruses in the pig population may instill a selective advantage to the intertype recombinant, and even an extremely rare nonhomologous recombination event could rapidly spread the virus in the pig population (73).…”
Section: Discussionmentioning
confidence: 99%
“…Each of these viruses replicates preferentially in macrophages and establishes a persistent infection in its natural host (54). Several members of the nidovirus order have been shown to undergo high-frequency recombination (50,81,83). Because of unique recombinatorial properties (81,83), widespread persistence, intermingling of virus types, and changes in swine management, PRRSV has been a key subject of evolutionary interest (17,18,19,33,39,67,69).…”
mentioning
confidence: 99%
“…Cell-culture studies have shown that recombination occurred within but not between genotypes in type 1 (van Vugt et al, 2001) and type 2 Yuan et al, 1999) PRRSV. Recombination was also demonstrated in animals Murtaugh et al, 2002).…”
Section: Recombinationmentioning
confidence: 99%